Crowding out effects of financial knowledge and attitude on risk preferences: Evidence from a least developed African country - Ruth Tacneng; Klarizze Anne Martin Puzon; Thierno Amadou Barry (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Using hand-collected survey and experimental data, we examine the determinants of financial literacy as well as the link between self-reported risk and elicited risk preferences in a least developed African country, Guinea. We measure financial literacy as the sum of three elements: financial knowledge, attitude, and behaviour. Our findings indicate that the lack of a significant relationship between our financial literacy measure and risk preferences is caused by the crowding out effects of financial attitude and knowledge. Individuals who display stronger financial knowledge are more willing to take on risk, but so are those with poor financial attitudes. Among individuals who have extensive financial knowledge, those with lower financial attitude scores or negative attitudes towards future planning and saving are more willing to take risks. These highlight the need to accentuate not only financial knowledge but also strong financial attitude and good financial behaviour to comprehensively and properly manage risks.
Keywords: D14; D81; O1; O55; 330; financial literacy; risk preferences; Africa